Self Love: A Counseling practice for Handling Self Injury - Eliya, Fitri; Anwar, Khairil; Harmaini, Harmaini; Masyhuri, Masyhuri (Educational Guidance and Counseling Development Journal, 2024)
Self-injury or self-harm is a form of negative behavior that harms oneself and can have a bad impact on mental health. The emergence of self-injury behavior as a form of emotional outburst to overcome pain that is too painful and cannot be expressed in words. One of the causes of self-injury behavior is a lack of self-love for oneself. Self love is a counseling effort that can be provided by counselors to deal with self-injury behavior. Self love is an important aspect in maintaining mental health. The application of self-love is very important in the lives of self-injurers. With an attitude of self-love, actors will better understand, accept and love themselves according to their condition as they are, can straighten out negative thought patterns that can harm themselves, can handle problems they face wisely, can be more responsible for the actions they take, and it will be easier to think positively when angry, sad, disappointed, or when facing problems in life.